Medical Marijuana – Airing Out the Smoke of Doubt - Karir, Aneesh (The Meducator, 2014)
On April 1, 2014, Canada will implement a drastically new set of regulations that will redefine the laws on the production and acquisition of medical marijuana, affecting over 35,000 patients nationwide. Patients will have to exclusively seek commercial vendors for medical marijuana and pay a much higher price compared to the costs of growing marijuana in their residences. This provides several benefits to the Canadian economy and protects against drug abuse, yet worries citizens and users who are trying to minimize costs. The Canadian government will require patients to obtain a prescription from a general physician, rather than a specialist, to gain access to medical marijuana. This new legislation therefore introduces a new source of pressure for general practitioners and makes them reluctant to support the bill. Still, with a plethora of viable solutions, such as increased safety and quality assurance for citizens who are wary about the new system, the commercialization of medical marijuana could prove to be a reasonable decision for the nation’s future.